Empirical Study of Entrepreneurship in Tijarah Concept - Linge, Abdiansyah; Ahmad, Upi Sopiah (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2021)
Economic activities including production, distribution and consumption are one of the ways humans meet their daily needs. Economic development is inseparable from the three economic activities, development is a multidimensional process that involves fundamental changes in social structures, social behavior and institutions. So, people can participate in the economy by creating full employment opportunities, everyone has the same abilities (equal productivity, equal access), and each behaves rationally (efficient). This study examines the Islamic economic view of the concept of entrepreneurship with an empirical literature approach, to explore the concept of entrepreneurship according to the tijarah concept contained in the Qur'an. In this study it can be understood that Islam views entrepreneurial activities as part of the work recommended in Islam to meet human economic needs. Entrepreneurial activity in Islamic view uses the equivalent of the word tijarah, there are provisions in Islam regarding the limitations that can be carried out in economic activity. Entrepreneurship that is driven by natural values ​​will become an economic activity that will be calculated before Allah, because Allah actually sees and takes into account what is done, including in economic activities